ДІАЛЕКТИКА ВЗАЄМОВІДНОСИН «Я»–«ІНШИЙ»–«ЧУЖИЙ» У ПОЛІКУЛЬТУРНОМУ ДИСКУРСІ СУЧАСНОСТІ - Культенко, В. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Досліджуються проблеми співіснування людей в сучасному глобальному світі в контексті актуальних дискурсів сучасності – полікультурності та мультикультуралізму, метою яких є подолати культурні суперечності у світі, допомогти людині включити іншого та чужого у свій життєвий світ, навчитись сприймати, чути, розуміти та співпереживати іншому-чужому, через нього відкриваючи й себе, поглиблюючи розуміння себе. Це є умовою нормального розвитку світу, в якому силові засоби, державні кордони та національні бар’єри не убезпечують від культурного протистояння, що часто доходить до своїх крайніх меж. Ключові слова: інший, чужий, полікультурність, мультикультуралізм, глобалізація, комунікація, солідаризм, толерантність. В.П.Культенко. Диалектика взаимоотношений «Я»-«Другой»-«Чужой» в современном поликультурном дискурсе. Исследуются проблемы сосуществования людей в современном глобальном мире в контексте актуальных дискурсов современности – поликультурности и мультикультурализма, целью которых является преодолеть культурные противоречия в мире, помочь человеку включить другого и чужого в свой жизненный мир, научиться воспринимать, слышать, понимать и сопереживать другому-чужому, через него открывая и себя, углубляя понимание себя. Это является условием нормального развития мира, в котором силовые репрессивные средства, государственные границы и национальные барьеры не ограждают от культурного противостояния, часто доходящего до своих крайних пределов. Ключевые слова: другой, чужой, поликультурность, мультикультурализм, глобализация, коммуникация, солидаризм, толерантность. V. Kultenko. Dialectic of relations «I»-«Other»-«Alien» in Modern polyculturals discourse. In this article the author investigates the problems of humans’ coexistence in the modern global world in the context of such actual discourses of modernity as polyculture and multiculture which aim is to defeat the cultural rivalries in the world, to help human with integration of other, alien things in its own life, to help with learning to realize, hear, understand other people. This is a condition of normal world development where military actions, state borders do not provide the isolations from cultural conflict, which often reaches to its extreme borders. With help of integration of others in your own life, the formation of such generally agreed rules of coexistence as moral and legal occurs. These moral and legal rules help to integrate each others freedom into the general unity, without violation of others’ liberty. Acceptance of other is possible with help of dialogue also with help of irrational ways of understanding such as religious belief, emotional affection, art, muscularity etc. This article also deals with philosophic positions of representatives of different streams, studies, philosophic traditions considering the solvation of the given problems, among other things article analyzes and compares positions of devotees of liberalism, comunitarism, solidarism ideology, each of those proposes system of fundamental values, which must be put into the base of social understanding, achievement of necessary balance of powers and interests in polycultural social environment. Key words: other, alien, polyculture, multicultural, globalization, communication, solidarism, tolerance.